Applications and Challenges of Big Data in Market Analytics - Yang, Yingxuan (Transactions on Economics, Business and Management Research, 2024)
This paper explores the applications and challenges of big data in market analysis. It first introduces the definition, characteristics and sources of big data, and analyzes in depth the impact of advances in big data technology on market analysis. It then discusses specific applications of big data in customer behavior analysis, market trend forecasting, competitive analysis, and product development innovation, and analyzes the challenges faced, such as data quality, privacy and security, technological complexity, and cost investment. Solutions and best practices are further explored, including improved data quality, enhanced data privacy security, technology innovation and tool optimization, and return on investment optimization. Finally, key success factors and strategies to address Big Data in market analytics are summarized by comparing success and failure cases. This paper aims to provide organizations with a comprehensive perspective on understanding and applying big data to drive long-term business success in a competitive market environment.